Caracterização de minérios de ferro por sensoriamento remoto no semiárido sergipano - Santos, Rafael Marllus dos (2023)
Remote sensing has presented a wide range of applications in recent years, among them there is the one that allows the identification of possible targets of minerals without the need to be present in the field, through the interaction between matter and the electromagnetic energy emitted by a certain source. In the regions of Canindé de São Francisco/SE and Gararu/SE there are indications of several occurrences of metallic minerals, such as lead (Pb), copper (Cu), manganese (Mn) and iron (Fe), and to identify these occurrences, magnetic data, band combination techniques and remote sensing image processing methods were used in the visible, near-infrared and short-wave infrared bands of the Landsat 8 and Sentinel-2 satellites. The results presented by the applied techniques showed different characteristics, indicating the possible identification of exposed targets of iron oxides, hydroxyl minerals and areas of vegetation. By comparing the results for the different regions, the presence of similar characteristics is noted, pointing to the possibility of the existence of ferrous minerals in both analyzed regions. To verify the results, samples were collected at specific points, previously defined, which were analyzed using elemental characterization by X-ray Fluorescence (FRX) and mineralogical characterization by X-ray Diffraction technique (XRD).